Development of digital-based learning videos using applications vyond on the subject of automotive fuel systems at vocational high school - Gintoro, Dedy; Ratnawati, Dianna; Hakiki, Muhammad; Fadli, Radinal; Pratama, Kukuh Wahyudin (Jurnal Taman Vokasi, 2024)
Abstract: The aim of this research is to develop digital-based learning videos using the vyond application on automotive fuel systems subjects at Manggala Tama Binangun Vocational School, Cilacap. This research is Research and Development (R & D) research. The development stage includes problem identification, data collection, product design, design validation, design revision, product creation, limited testing, product revision 1, readability testing, product revision 2, and product ready for use. The data collection instrument uses a non-test instrument in the form of a questionnaire. The data analysis technique used is descriptive data analysis technique. The descriptive research results show that (1) The results of this research are in the form of learning videos on the subject of automotive fuel systems for class XI students at SMK Manggala Tama Binangun Cilacap. The development steps are problem identification, student analysis, concept analysis and formulation of learning objectives. The learning media design consists of four learning activities and each learning activity is equipped with learning objectives, introduction, material description, summary and evaluation questions. (2) Based on the analysis of the assessment results of material expert lecturers in the learning aspect it is classified as good with a score of 2.80 in the score range between > 2.50 to 3.25 and in the content aspect it is classified as fair with a score of 2.07 in the score range between > 1.75 to 2.50. Based on the results of the media expert's assessment in the visual appearance aspect, an average score of 3.23 was obtained in the score range between > 2.50 to 3.25 in the good criteria and in the media integration aspect, an average score of 3 was obtained in the score range between > 2.50 s. /d 3.75 on good criteria. It can be concluded that the results of the media expert's assessment on the media integration aspect are classified as good.   Keywords: Vyond Application; Development; Automotive Fuel System; Learning Video